OPTIMALISASI PENGGUNAAN MEDIA INTERAKTIF DIGITAL DALAM PEMBELAJARAN MATEMATIKA DI SEKOLAH DASAR UNTUK MENINGKATKAN KETERLIBATAN DAN HASIL BELAJAR SISWA - Adeilla Najwa Salsabila; Ifnur Fadhilla Legthonia; Mellyza Azzara; Supriyad; Jody Setya Hermawan (Universitas Muhammadiyah Kuningan, 2025)
This research aims to explore the application of digital interactive media in improving mathematics learning outcomes in elementary schools. The method employed is qualitative research, with data collection techniques involving a literature review of 15 peer-reviewed journal articles published between 2014 and 2024. The data is analyzed in depth to identify patterns, themes, or relationships relevant to the research topic. Data collection techniques include content analysis of articles related to the use of interactive digital media in mathematics learning. The instrument used in this study is an analysis form designed to evaluate the quality and impact of interactive media in the context of mathematics education. The analysis results indicate that the use of digital interactive media, such as educational applications and learning videos, can significantly enhance students' motivation and understanding of mathematical concepts. The use of appropriate media not only addresses students' negative perceptions of mathematics but also increases engagement and provides a more enjoyable learning experience. These findings highlight the importance of integrating technology into mathematics education to create a more effective and interactive learning process, which positively impacts students' learning outcomes.